Development and Validation of Simple RP-HPLC Method for Intracellular Determination of Fluconazole Concentration and Its Application to the Study of Candida albicans Azole Resistance - Tigran K. Davtyan; Levon A. Melikyan; Nune A. Nikoyan; Hripsime P. Aleksanyan; Nairi G. Grigoryan (International Journal of Analytical Chemistry)
Candida albicans (strains NCTC-885-653 and ATCC-10231) long-term cultivated in the presence of antifungal agent fluconazole (FLC) and classical microbiological methods for determination of minimal inhibitory concentration (MIC) were used in this study. A simple and sensitive method based on reverse-phase high-performance liquid chromatography (RP-HPLC) has been developed for the determination of FLC intracellular concentration in C. albicans using tinidazole as an internal standard. Following extraction with dichloromethane, the chromatographic separation was achieved on a Machery-Nagel EC250/2 Nucleodur-100-3 C18 column by gradient elution using the mobile phase consisting of (A) 0.01 M ammonium acetate buffer, pH = 5.00, and (B) acetonitrile. Different analytical performance parameters such as linearity, precision, accuracy, limit of quantification (LOQ), and robustness were determined according to US DHHS FDA and EMEA guidelines. The method was linear for FLC (r=0.9999) ranging from 100 to 10000 ng/mL. The intraday and interday precisions (relative standard deviation) were within 2.79 and 2.64%, respectively, and the accuracy (relative error) was less than 2.82%. The extraction recovery ranged from 79.3 to 85.5%. The reliable method was successfully applied to C. albicans azole-resistance study and it was shown that intracellular concentration of FLC correlated with a yeast drug susceptibility profile and MIC values.